(untitled) (Nepalese Journal of Radiology, 2013)
Medial canal fibrosis is an interesting type of acquired meatal atresia that is characterized by formation of a solid core of fibrous tissue in the medial part of the external auditory meatus abutting the tympanic membrane. A review of the literature showed that many different terms have been used interchangeably to report the same or similar condition. This is a case of medial canal fibrosis being reported to emphasize the importance in diagnosing this rare but easily treatable disease. A 16 yrs old female presented with bilateral conductive hearing loss & history of recurrent rhinitis & sinusitis. CT Temporal bone showed soft tissue density lesions in bilateral bony EAC (External auditory canal) with no bony erosion & normal middle ear. A diagnosis of Medial canal fibrosis was given. The patient was operated & biopsy of the specimen came out to be inflammatory granulation tissue. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 69-71 DOI: http://dx.doi.org/10.3126/njr.v2i2.7689